The Use of Iron Oxide Nanoparticles to Reprogram Macrophage Responses and the Immunological Tumor Microenvironment - Mulens-Arias, Vladimir; Rojas, José Manuel; Barber, Domingo F. (Frontiers in Immunology, 2021)
The synthesis and functionalization of iron oxide nanoparticles (IONPs) is versatile, which has enhanced the interest in studying them as theranostic agents over recent years. As IONPs begin to be used for different biomedical applications, it is important to know how they affect the immune system and its different cell types, especially their interaction with the macrophages that are involved in their clearance. How immune cells respond to therapeutic interventions can condition the systemic and local tissue response, and hence, the final therapeutic outcome. Thus, it is fundamental to understand the effects that IONPs have on the immune response, especially in cancer immunotherapy. The biological effects of IONPs may be the result of intrinsic features of their iron oxide core, inducing reactive oxygen species (ROS) and modulating intracellular redox and iron metabolism. Alternatively, their effects are driven by the nanoparticle coating, for example, through cell membrane receptor engagement. Indeed, exploiting these properties of IONPs could lead to the development of innovative therapies. In this review, after a presentation of the elements that make up the tumor immunological microenvironment, we will review and discuss what is currently known about the immunomodulatory mechanisms triggered by IONPs, mainly focusing on macrophage polarization and reprogramming. Consequently, we will discuss the implications of these findings in the context of plausible therapeutic scenarios for cancer immunotherapy.